Antecedents of project managers' voice behavior: The moderating effect of organization-based self-esteem and affective organizational commitment. Issue 6 (August 2016) - Ekrot, Bastian; Rank, Johannes; Gemünden, Hans Georg
Abstract: Theory and research stress that employee voice behavior (VB; discretionary communication of ideas, suggestions, or concerns with the intent to improve organizational functioning) positively influences decision making, improvement, and innovation. However, the VB construct has rarely been studied in the specific context of project management. Using a sample of 618 project managers and 154 project portfolio coordinators nested in 154 firms, the main purpose of this study was to analyze a moderated model, in which specific contextual factors interact with individual-level variables to predict project managers' VB. Consistent with our hypotheses derived from self-consistency theory, moderated hierarchical regression analysis revealed that idea encouragement, career perspectives, qualification opportunities, and peer collaboration related more positively to VB for project managers with a high level of organization-based self-esteem. For project managers high in affective organizational commitment, we found stronger positive relationships of peer collaboration and idea encouragement with project managers' VB. Highlights: Investigation of voice behavior in the context of project managers Simultaneous consideration of contextual and person-level factors to affect voice Emphasizing the importance of project managers' psychological states Application of established theories from the realm of organizational behavior